Industrial Training Report: Perpustakaan Tuanku Bainun Universiti Pendidikan Sultan Idris / Fatin Nadiah Mohamed Fuad - Mohamed Fuad, Fatin Nadiah (Faculty of Information Management, 2018)
Industrial training is an important phase of a student life. A well planned, properly executed and evaluated industrial training helps a lot in developing a professional attitude. It develops an awareness of industrial approach to problem solving, based on a broad understanding of process and mode of operation of organization. The aim and motivation of this industrial training is to receive discipline, skills, teamwork and technical knowledge through a proper training environment, which will help me, as a student in the field of Information Management, to develop a responsiveness of the self-disciplinary nature of working world. During a period of five months training at Perpustakaan Tuanku Bainun, Throughout this industrial training, I have been learned new skills especially in technical work, build confident when dealing with people, improve communication skills and able to implement what I have learnt as a Degree in Information Management student in UITM Rembau.